Biliary interventions using single‐operator cholangioscopy. Issue 5 (21st March 2019) - Navaneethan, Udayakumar; Moon, Jong Ho; Itoi, Takao
Abstract : Cholangioscopy provides an opportunity to directly visualize the bile duct for diagnosing biliary lesions and for therapeutic interventions. Although there are different cholangioscopy techniques available, single‐operator cholangioscopy has gained widespread acceptance as the standard technique for interventions in the biliary system because of its ease of use and widespread availability. Single‐operator cholangioscopy can be used for both diagnostic and therapeutic indications in the biliary tract. Diagnostic cholangioscopy is used for direct evaluation of indeterminate bile duct strictures with biopsies, diagnosing filling defects in the bile ducts observed during endoscopic retrograde cholangiography (ERC) imaging, preoperative mapping of the precise location and extension of tumors of the biliary tract, and diagnosis of intraductal neoplasms. Therapeutic cholangioscopy is used for visually guided treatment of biliary stones that have failed extraction with conventional ERC techniques, residual or impacted stones by using intraductal lithotripsy, ablation of biliary tumors and for facilitation of guidewire advancement into selective intrahepatic ducts for adequate biliary drainage. In this review, we will focus on advances in the single‐operator cholangioscopy techniques in the diagnosis and management of biliary disorders.